Prenatal diagnosis using combined quantitative fluorescent polymerase chain reaction and array comparative genomic hybridization analysis as a first‐line test: results from over 1000 consecutive cases. (22nd April 2013) - Scott, F.; Murphy, K.; Carey, L.; Greville, W.; Mansfield, N.; Barahona, P.; Robertson, R.; McLennan, A.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2013:41:489